Tren Penelitian Sejarah Lisan dan Dokumentasi di Indonesia: Analisis Bibliometrik di SCOPUS (2013-2023) - Sofia Nur Aisyah; Tamara Adriani Salim; Frans Asisi Datang; Muhammad Prabu Wibowo (Perpustakaan Nasional, 2023)
This research discusses research trends on the topic of oral history and documentation in Indonesia. The focus of the discussion is (1) how much relevant research is related to the topic of discussion of oral history and documentation; (2) what are the research trends in oral history and documentation; and (3) what are the implications for research on similar topics in the future and the implications for research in Indonesia. This research uses a bibliometric analysis method by taking data from the SCOPUS database with search filters related to the topic of oral history and documentation for the last ten years, or 2013–2023. Then it was analyzed further using VOSviewer to see the network and density of research on similar topics. The results show that the highest number of publications related to the topic of oral history and documentation is in 2022, with 21 publications; the country with the most contribution is the United States with 46 publications; the field of social sciences is the subject with the largest contribution of 37.9%; and the most common documents were articles at 58.3%. Seeing from the network and density analysis that the topic of oral history and documentation is related to other keywords and has the opportunity to be further researched is also an interesting discussion.